THE ROLE OF TEACHERS IN INSTILLING ISLAMIC CHARACTER VALUES THROUGH ROUTINE ACTIVITIES AT SCHOOL - Habibie, Rizky Septi Maulana; Chotib, Moch.; Mustajab, Mustajab (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The cultivation of Islamic character values in the school environment is one of the important missions in value-based education. This article aims to examine the role of teachers in shaping Islamic character through routine activities at school. This research uses a descriptive qualitative approach with a case study method in several Islamic-based schools. Data were obtained through interviews, observations and documentation. The results show that routine activities such as congregational prayers, recitation of the Qur'an, and discussion of Islamic values are effective in building students' character. This article recommends close collaboration between teachers, students, and parents in supporting the formation of a solid Islamic character.